Market Efficiency in the Kuala Lumpur Stock Exchange: Further Evidence Using Garch Model - Aru Bol, Victoria Samuel (2001)
The recent Asian currency crisis has revived the debate about the efficacy of the weak-form efficient market hypothesis as an appropriate tool for testing the volatility of the stock markets. This is because the idea that securities markets are efficient is a fundamental factor that affects not only the investment decisions but also all financial dealings in financial business. This study tested the weak-form version of efficient market hypothesis using the generalized autoregressive conditional heteroskedastic (GARCH) model on the monthly data of returns of stocks of listed under Kuala Lumpur Stock Exchange Market for the period 1994-99. In the pre-crisis results, GARCH effect was evident in 24 out of 30 companies (80%), suggesting that homoskedasticity (constant variance) hypothesis is rejected. In addition, the diagnostic test results indicated that the residuals were found to be uncorrelated for 26 out of 30 companies, while only 19 companies (63%) found to be to be normally distributed.The results of GARCH model during the crisis period were less evident, only 14 out of30 companies (slightly less than 50%) exhibit GARCH effect. Beside this, during the crisis period, only 20 out of 30 companies were not normally distributed, whereas 28 out of 30 companies have shown no autocorrelation, suggesting that weak form market hypothesis cannot be rejected. The results suggest that the characters of time series of the two periods have changed substantially during the crisis period but as the diagnostic test has shown, we cannot reject the weak form efficient market hypothesis for both periods.